2021
DOI: 10.3389/fpsyg.2021.701189
|View full text |Cite
|
Sign up to set email alerts
|

The Well-being and Instructional Experiences of K-12 Music Educators: Starting a New School Year During a Pandemic

Abstract: In adapting to remote emergency teaching modes during pandemic-imposed conditions, teachers’ instruction has changed dramatically. Early research indicates that the well-being of music teachers has suffered during the COVID-19 pandemic and that high levels of depression are widespread. The purpose of this survey study was to assess the continued psychological well-being of music teachers working amid a global pandemic based upon previous research we conducted during the Spring 2020 semester when most teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…Specific to music education, there appears to be little extant research regarding psychological well-being among K-12 and university music teachers (e.g., Kang & Yoo, 2019; Kelley et al, 2022; Miksza et al, 2021; Parkes et al, 2021). As far as we can determine, there is no research that specifically explores the well-being of music teacher educators.…”
Section: Well-being and Adaptability In Music Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific to music education, there appears to be little extant research regarding psychological well-being among K-12 and university music teachers (e.g., Kang & Yoo, 2019; Kelley et al, 2022; Miksza et al, 2021; Parkes et al, 2021). As far as we can determine, there is no research that specifically explores the well-being of music teacher educators.…”
Section: Well-being and Adaptability In Music Educationmentioning
confidence: 99%
“…In contrast to competence and relatedness, work engagement was not found to be a predictor of well-being; a finding that Kang and Yoo describe as inconsistent with other research. Miksza and colleagues (2021) and Parkes and colleagues (2021) explored the impact of the COVID-19 pandemic on teachers’ psychological well-being. In both studies, the researchers found that teachers reported lower levels of well-being and higher levels of depression than published norms.…”
Section: Well-being and Adaptability In Music Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers were also part of the Emergency Remote Teaching process, and their experience is discussed in recent articles (Alqabbani et al, 2020), as well as compared to the students' perceptions (Zhao et al, 2021). In one article, the purposes was to explore the ways that pandemic conditions have affected music teachers' sense of safety at work and their current teaching situations, and conclusions indicate that the teachers' well-being has gotten worse from the start of the pandemic through the start of a new school year in fall 2020 (Parkes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…D. Shaw, 2014). These concerns deepened as large ensembles were restricted or moved online during the ongoing COVID-19 pandemic (Hash, 2021; Parkes et al, 2021).…”
mentioning
confidence: 99%